The 1820s Marks a Shift to Hotter‐Drier Summers in Western Europe Since 1360 - Lu Wang; Hongyan Liu; Deliang Chen; Peng Zhang; Steven Leavitt; Yu Liu; Congxi Fang; Changfeng Sun; Qiufang Cai; Zhengyang Gui; Boyi Liang; Liang Shi; et al. (Geophysical Research Letters)
Abstract Recent soil moisture (SM) reconstructions revealed plunging trends and enhanced SM‐temperature couplings over the last two decades in dry regions. However, how SM changed and whether the land‐atmosphere interaction was intensified over time in humid regions remained unknown. Here we reported the first six‐century‐long regional summer SM reconstruction (1360–2000 CE) in western Europe (WE) using three individual tree‐ring δ18O chronologies in England and France. A sharp wet‐to‐dry change occurred around 1820, earlier than 1850–1900 CE, the commonly used historical baseline of anthropogenic climate changes. Enhanced coupling of SM‐temperature followed, with stronger summer sea level pressure anomalies in dry years after the 1820s. Our results reveal that the hotter‐drier regime has also become more frequent in humid WE under global warming.